TRAIL Enhances Apoptosis of Human Hepatocellular Carcinoma Cells Sensitized by Hepatitis C Virus Infection: Therapeutic Implications - Jang, Jae Young (Public Library of Science, 2014)
Hepatitis C virus (HCV) infection causes chronic liver diseases leading to hepatocellular carcinoma (HCC) and liver failure. We have previously shown that HCV sensitizes hepatocytes to mitochondrial apoptosis via the TRAIL death receptors DR4 and DR5. Although TRAIL and its receptors are selective targets for cancer therapy, their potential against HCC with chronic HCV infection has not been explored yet. Here we show that HCV induces DR4/DR5-dependent activation of caspase-8 leading to elevation of apoptotic signaling in infected cells and also present TRAIL effect in HCV-induced apoptotic signaling. HCV induced proteolytic cleavage of caspase-9 by stimulating DR4 and DR5, resulting in subsequent cleavage of caspase-3. Further, HCV-induced proteolytic cleavage in caspase-8, caspase-9, and caspase-3 was enhanced in the presence of recombinant TRAIL. HCV-induced cleavage in caspase-9 and increase in caspase-3/7 activity was completely suppressed by silencing of either DR4 or DR5. Perturbing DR4/DR5-caspase-8 signaling complex by silencing DR4 and DR5 or by chemical inhibitor specific to caspase-8 led to decrease of HCV-induced cleavage of poly(ADP-ribose) polymerase (PARP), a substrate for caspase-3 during apoptosis, indicating the functional role of caspase-8 in HCV-induced apoptotic signaling network. Furthermore, TRAIL enhanced PARP cleavage in apoptotic response induced by HCV infection, indicating the effect of TRAIL for the induction of selective apoptosis of HCC cells infected with HCV. Given the importance of apoptosis in HCC development, our data suggest that HCV-induced DR4 and DR5 may be considered as an attractive target for TRAIL therapy against HCC with chronic HCV infection.